Pengaruh Marketing Mix Terhadap Loyalitas Konsumen J&C Cookies di Surabaya - Sosio Prastiwi (Yos Soedarso Economic Journal (YEJ), 2019)
The purpose of this study was to determine the effect of marketing mix on consumer loyalty of J&C Cookies in Surabaya. To find out the variables of the marketing mix (product, price, promotion and place) simultaneously, partially and dominantly affect consumer loyalty in Surabaya. While the method used is multiple linear regression analysis and hypothesis testing. Based on the analysis there is a significant influence of marketing mix (product, price, promotion and place) on consumer loyalty of J&C Cookies in Surabaya. The most dominant variable influencing consumer loyalty is the promotion of the reason consumers can easily see their products in various media that can be accessed throughout Indonesia and even the world.Â Keywords: Product; Price; Promotion; Place; Customer Loyalty